Perbedaan Kadar serum Liver-Type Fatty Acid Binding Protein (L-FABP) dan Beta Trace Protein (BTP) Dalam Serum Sebelum dan Saat Cedera Ginjal Akut - Mona Yuliari; Hani Susianti; Deasy Ayuningtyas Tandio (DiscoverSys Inc., 2022)
Background: The prevalence of Acute Kidney Injury (AKI) varies, ranging from 3% to 20% of hospitalized patients and 25% to 67% of ICU patients, with 5% to 6% of the ICU population requiring renal replacement therapy following AKI. Establishing the diagnosis of AKI with KDIGO criteria using serum creatinine marker. Serum creatinine has a sensitivity of 52.9% and a specificity of 85.7% for AKI. The Sensitivity and specisifity of serum creatinine is not good because it can increase without any real injury or do not change even though acute tubular injury has occurred due to compensation for increased function by the remaining nephrons. L-FABP (Liver type Fatty Acid Binding Protein) and BTP (Beta Trace Protein) serum are newly discovered biomarkers potential for the early diagnosis of acute kidney damage. This study was conducted to determine the change in L-FABP and BTP concentration levels as markers of AKI. Method: This study is a longitudinal observational study with patients suffering from AKI with serum samples taken before and after an increase in serum creatinine level of ≥0.3 mg/dL in 48 hours. Serum levels of L-FABP and BTP were examined by ELISA method, and serum creatinine by enzymatic colorimetric. Differences between levels before and during AKI were analyzed by the Wilcoxon test. Results: The number of research subjects was 40 people. There was significant difference between serum creatinine before and during AKI (1.97 (1.36-2.77) mg/dL vs. 3.52 (2.53-4.91). mg/dL, p<0.001). Indeed there were also significant differences in serum L-FABP before and during AKI (3775.48 (1614.11-5086.68) ng/mL vs. 5427.28 (4562.79-5765.14) ng/mL, p<0.001), and serum BTP levels before and during AKI (456.36 (290.35-591.67) mg/L vs. 518.38 (436.37-691.90) mg/L, p<0.001). Conclusion: Serum levels of L-FABP and BTP increased significantly in the condition of the AKI so that it has the potential to be a marker for the diagnosis of AKI. Latar belakang: Prevalensi cedera ginjal akut (Acute Kidney Injury/AKI) bervariasi, sekitar 3% hingga 20% dari pasien rawat inap dan 25% hingga 67% dari pasien ICU, dengan 5% hingga 6% dari populasi ICU membutuhkan terapi penggantian ginjal setelah terjadi AKI. Penegakan diagnosis AKI dengan kriteria KDIGO menggunakan marker serum kreatinin. Serum kreatinin mempunyai sensitivitas 52,9% dan spesifisitas 85,7% untuk AKI. Sensitivitas dan spesifisitas serum kreatinin tersebut kurang baik karena kadar serum kreatinin dapat meningkat tanpa ada cedera nyata maupun tidak berubah meskipun telah terjadi cedera tubulus akut karena adanya kompensasi peningkatan fungsi oleh nefron yang tersisa. Serum L-FABP (Liver type Fatty Acid Binding Protein) dan BTP (Beta Trace Protein) adalah biomarker yang ditemukan untuk diagnosis dini AKI. Penelitian ini dilakukan untuk mengetahui perubahan kadar serum L-FABP dan BTP sebagai penanda terjadinya AKI. Metode: Penelitian ini adalah penelitian observasional longitudinal dengan subyek pasien yang menderita AKI dengan sampel serum yang diambil sebelum dan sesudah terjadi peningkatan kadar serum kreatinin ≥0,3 mg/dL dalam 48 jam. Kadar serum L-FABP dan BTP diperiksa dengan metode ELISA, dan serum kreatinin dengan metode enzimatik kolorimetrik. Perbedaan antara kadar sebelum dan saat AKI dianalisis dengan uji Wilcoxon. Hasil: Jumlah subyek penelitian adalah 40 orang. Terdapat perbedaan bermakna antara kreatinin serum sebelum dan selama AKI (1,97 (1,36-2,77) mg/dL vs 3,52 (2,53-4,91), mg/dL, p<0,001. Teradapat juga perbedaan yang signifikan dalam serum L-FABP sebelum dan selama AKI (3775,48 (1614,11-5086,68) ng/mL vs 5427,28 (4562,79-5765,14) ng/mL, p<0,001), dan kadar BTP serum sebelum dan selama AKI (456,36 (290,35-591,67) mg/L vs. 518,38 (436,37-691,90) mg/L, p<0,001). Simpulan: Kadar serum L-FABP dan BTP meningkat signifikan pada kondisi AKI sehingga berpotensi menjadi marker untuk diagnosis AKI.